Berpikir Intuitif sebagai Solusi Mengatasi Rendahnya Prestasi Belajar Matematika - Sofia Sa'o (JRPM (Jurnal Review Pembelajaran Matematika), 2016)
One of the factors that are important to achieve the goals of mathematics learning is a way of thinking students during learning. One of the processes used are intuitive thinking. Intuitive thinking is a cognitive process that led to the idea as a strategy for making decisions in solving problems. Spontaneous answers both written and oral expression so that students solve mathematical problems without the use of analytical thinking. The purpose of this study was to describe the solution to overcome the lack of mathematics achievement by means of intuitive thinking. The method used is qualitative to describe the solution of the subject in intuitive thinking. The subject was the four student of class VIII. Subjects using antisipatory intuitive ways of thinking that is contrary to the alleged problem solving in general and included in the global components and perception because it produces the correct answer with the solution.